Global production networks in the modern world economy: theory and current trends - Shalupayeva, Natallia S. (Journal of the Belarusian State University. Economics, 2023)
At present, the international production is becoming one of the most important factors influencing the development of all forms of international economic relations. The deepening of the international fragmentation of production has led to the fact that in the modern world economy 80 % of international trade flows are concentrated within the framework of global production networks, participation in them determines the competitiveness of countries, their investment attractiveness and role in the international division of labour and the world reproduction process. The article explores the theoretical foundations of global production networks development, reveals the essential differences between global value chains and global production networks, their types and types of countries’ involvement. A number of trends in the development of global production networks, as well as the features of participation of China in them are identified. It is shown that the economic development of China has changed the topology of global production networks in the world and in the Asia – Pacific region, both at the aggregate level and at the sectoral level of the economy.
Keywords: global value chain; global production network; multinational enterprise; international production; foreign direct investment; China